The Future of Land Warfare - O'Hanlon, Michael E. (Book collections on Project MUSE., 2015)
What happens if we bet too heavily on unmanned systems, cyber warfare, and special operations in our defense?In today's U.S. defense policy debates, big land wars are out. Drones, cyber weapons, special forces, and space weapons are in. Accordingly, Pentagon budget cuts have honed in on the army and ground forces: this, after the long wars in Iraq and Afghanistan, seems like an appealing idea. No one really wants American boots on the ground in bloody conflicts abroad. But it is not so easy to simply declare an end to messy land wars. A survey of the world's trouble spots suggests that land war.